Patriarki Dalam Iklan Rabbani: Analisi Wacana Kritis Pada Iklan Rabbani Di Instagram - Aflakha Tazakka Susanto; Novita Haryono (Universitas Sebelas Maret (UNS), 2024)
In addition to its economic functions, advertising serves as a space where meanings about the reality of the world are constructed and formed, thus carrying hidden messages. The Rabbani ads on Instagram caught the attention of researchers because they target a female audience but portray women in a patriarchal cultural context that is detrimental to women. This study aims to understand how Rabbani ads construct patriarchal cultural practices. The method used in this research is a qualitative study that employs Norman Fairclough's critical discourse analysis model, which consists of three stages: the descriptive text stage, where discourse is viewed from the text; the interpretive stage, where discourse is seen as a discursive practice; and the explanatory stage, where discourse is seen as a sociocultural practice. In analyzing the Rabbani ads, the researcher also referred to Nancy Hartsock's Standpoint Feminism theory. The data collection technique used is a literature study and an interview. The study reveals that at the textual level, Rabbani ads contain patriarchal discourse. This patriarchal discourse is shown through stereotypical and subordinative portrayals of women's roles and characters. At the discursive practice level, the Rabbani ad producers construct women with controversial and relevant content to increase the popularity of the products offered. From the consumer's perspective, the audience's interpretation is generally the same as the researcher's analysis of the text. At the sociocultural level, the target market character and gender ideology influence how Rabbani constructs women in its ads. The results of this study are expected to make advertisers more aware and sensitive to gender issues in their surroundings, as they have the power through media to create and sustain values in society.